Public Administration Singapore Style - Quah, John S.T (Talisman, 2010)
Singapore was ranked first for the competence of its public officials from 1999 to 2002 by the Global Competitivenes Report. While research has been done on various aspects of public administration in Singapore., there is to date no comprehensive study of the Singapore civil service and the statutory boards and their contribution to the attainment of national development goals.